MODIFICATION OF NANO CHITOSAN AND POLYURETHANE ON THE THICKNESS AND THERMAL STABILITY OF LITHIUM ION BATTERY SEPARATORS - Wahyudi, Kiki Salsa Nabila; Rihayat, Teuku; Putra, Alfian (Politeknik Negeri Lhokseumawe, 2025)
This study aims to modify lithium-ion battery separators using a combination of polypropylene (PP), polyurethane (PU), and nano chitosan, and to evaluate the effects of varying composition ratios and soaking time on thickness and thermal stability. The separators were fabricated using the casting method with variations in the PP:PU:Nano Chitosan ratio (4:1:5, 4:2:4, 4:3:3, 4:4:2, and 4:5:1) and soaking times of 1–5 days. Characterization included thickness (Digital Thickness Gauge), thermal stability (thermal shrinkage test and TGA), and surface morphology (SEM). The results showed that a 4:3:3 ratio with 3 days of soaking produced the best performance, with a thickness of 23–25 µm, low thermal shrinkage (0.5%–2.1%), degradation onset at 370.10 °C, degradation peak at 429.73 °C, and a dense and uniform morphology with well-distributed pores. This formulation is recommended as a potential separator for lithium-ion battery applications.Keywords: Battery, Lithium-ion, Nano Chitosan, Polypropylene, Polyurethane, Separator